The impact of the legal nature of the product of thought on the ways of transmission (Damascus University Journal for legal sciences, 2025)
The various jurisprudential opinions that have been raised about the nature of intellectual property rights, whether related to literary and artistic ownership, or industrial property, some of which discussed the possibility of considering the product of mind as property or not, and others discussed whether this product can be given to its owner. A real right or a financial right, and what jurisprudence has reached thanks to the famous ruling issued by the French Court of Cassation, considering it a product of mind, gives its owner a right with a mixed nature that combines a financial right and a real right. Each of these rights has a special nature, and provisions differ from one right to another. This special, mixed nature of intellectual property rights will also result in a mechanism for transmission through inheritance that differs from the rules for the transmission of real rights and financial rights
Keywords: Intellectual Property; Literary And Artistic Property; Industrial Property; Moral Right; Financial Right; Inheritance